2017
DOI: 10.1007/s11356-017-0359-6
|View full text |Cite
|
Sign up to set email alerts
|

Rare-earth elements in human colostrum milk

Abstract: Rare-earth elements (REEs) are used in a growing number of applications, and their release to environment has increased over the decades. Knowledge of REEs in human milk and factors that could possibly influence their concentration is scarce. This study evaluated the concentrations of 16 REEs (Ce, Eu, Er, Gd, La, Nd, Pr, Sc, Sm, Dy, Ho, Lu, Tb, Tm, Y, and Yb) in human colostrum milk collected from Polish women (n = 100) with the ICP-OES technique. The concentrations (mean ± SD) of Pr (41.9 ± 13.2 μg L −1 ), Nd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 42 publications
(47 reference statements)
0
10
0
Order By: Relevance
“…To the best of our knowledge, the present study is the first to analyze the level of REEs in microalgal food supplements. They represent an emerging group of pollutants whose emissions have risen over recent decades due to certain human activities (Pagano et al 2015) resulting in increased human exposure via different routes (Poniedziałek et al 2017). The outcomes of these exposures are yet to be fully explored, although selected REEs reveal cytotoxicity and have been potentially linked to anti-testicular effects, male sterility, hypertension in females, reduced IQ, and neurological alterations in children (Zhu et al 1996;Marzec-Wróblewska et al 2015;Wang et al 2017;Gwenzi et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the present study is the first to analyze the level of REEs in microalgal food supplements. They represent an emerging group of pollutants whose emissions have risen over recent decades due to certain human activities (Pagano et al 2015) resulting in increased human exposure via different routes (Poniedziałek et al 2017). The outcomes of these exposures are yet to be fully explored, although selected REEs reveal cytotoxicity and have been potentially linked to anti-testicular effects, male sterility, hypertension in females, reduced IQ, and neurological alterations in children (Zhu et al 1996;Marzec-Wróblewska et al 2015;Wang et al 2017;Gwenzi et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…It consists of nine elements (La, Ce, Eu, Gd, Nd, Pr, Pm, Sm, and Sc) categorized as light REEs, and 8 elements (Dy, Er, Ho, Lu, Tb, Tm, Y, and Yb) representing heavy REEs. Numerous applications of REEs in the medical, industrial, and agricultural sectors have been developed over recent decades resulting in their increasing environmental levels (Pagano et al., ; Poniedziałek et al., ). The data concerning their toxicity is scarce and mostly limited to Ce, La, Nd, and Gd.…”
Section: Contamination Levelmentioning
confidence: 99%
“…Moreover, Zhang et al (2020) evidenced that smoking was positively associated with Dy, Er, and Yb levels, whereas drinking habits showed no significant effect on REE levels, while La, Ce, Pr, and Nd were higher in hair and nails of smokers (Rodushkin and Axelsson, 2000). Poniedziałek et al (2017) found that Nd concentration was significantly higher in the colostrum milk of smoking women compared to those who had never smoked. Zhang et al (2020) confirmed also that REE levels are higher in biological matrices of smokers, but not in drinkers.…”
Section: Figurementioning
confidence: 94%